The Effectiveness of Yoga Therapy on Early Maladaptive Schemas and Emotional Distress of Depressed Women: A Semi Experimental Study - Sahar Saeidi Asl; Fatemeh Sadat Robati (Hamadan University of Medical Sciences, 2021)
Introduction: Using yoga movements helps depressed women to become aware of and control their minds and emotions. The aim of this study was to investigate the effectiveness of yoga therapy on early maladaptive schemas and emotional distress of depressed women in Tehran. Methods: This study was a quasi-experimental study with a pre- and post-test design with a control group. The statistical population of the study included all depressed women referring to Omid and Rah-e-Farda counseling centers in the first half of 2019 in Tehran, Iran. The sampling method was available sampling. The sample size was at least 10 based on the type of research that was considered in the experimental research for each group. The sample was 30 subjects who were randomly divided into two groups of experimental (15 people) and control (15 people). The research tools included the Yang Inconsistent Schema Questionnaires (2005) and Toronto's Emotional Disappointment (2005). To analyze the data, mean, standard deviation and covariance analysis were used using SPSS 23. P-value less than 0.05 was considered significant. Results: In the cut-off and exclusion variables in the pre-test of the intervention group, the mean and standard deviation were 2.85±21.03, in the control group 3.50±16.46, in the cut-off and exclusion variables in the post-test of the intervention group, the mean and standard deviation was 4.28±15.28, in the control group 3.28±15.28, in the variable of disturbed restrictions in the pre-test of the intervention group, the mean and standard deviation were 3.72±12.63, in the control group 30±17.80 3. In the disturbed constraint variable in the post-test of the intervention group, the mean and standard deviation were 4.43±17.76, in the control group was 3.76±17.90, and in the emotional malaise variable in the pre-test of the intervention group, the mean and standard deviation of 49.80.±37.67, in the control group 52.86±36.51, in the variable of disturbed constraints in the post-test of the intervention group, the mean and standard deviation of 13.06.±23.73, in the control group 33.37±76.3, was obtained. The results showed that there was a significant difference between the scores of incompatible schemas, emotional inadequacy and psychological health of the experimental and control group in the post-test stage (P <0.01). Conclusions: Thus, yoga therapy is an effective treatment for maladaptive schemas, emotional distress, and of depressed women.